AN ANALYSIS OF REWARD AND PUNISHMENT EFFECTS TOWARDS LECTURER PERFORMANCE AT STMIK ROYAL USING SPSS SOFTWARE - Pristiyanilicia Putri (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The need for optimal implementation of reward and punishment on the STMIK Royal campus is a real problem at the current institutional management level. This can be seen from interviews with several STMIK Royal lecturers, where rewards tend to be more dominant than punishment, which has yet to be applied consistently. Given these problems, this study aims to analyze and find out how the application and influence of reward and punishment have on the performance of lecturers at STMIK Royal. The research method used in this study used a quantitative approach where the data collection instruments used were questionnaires or questionnaires and interviews. The data comes from the permanent lecturer population at STMIK Royal Kisaran in 2023, namely 83 lecturers. The sampling technique used was saturated sampling so that the samples in this study were all of the population taken, totaling 83 respondents. The analytical method uses multiple regression analysis by conducting the F-test and t-test, where the data is processed using the SPSS software. The equation Y = 17.033 + 0.148 X 1 + 0.803 X 2 is obtained from multiple regression analysis results. Simultaneously the reward and punishment variables affect lecturer performance by 35.2%. But partially, only the punishment variable affects the lecturer performance variable, while the reward variable has no partial effect on the lecturer performance variable at STMIK Royal